2015
DOI: 10.1007/s00122-015-2455-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and genetic characterization by high-throughput SNP analysis of intervarietal substitution lines of rapeseed (Brassica napus L.) with enhanced embryogenic potential

Abstract: Key messageSeven intervarietal substitution lines were identified with embryogenic potentials up to 40.4 times that of the recurrent parent, providing an ideal material for further in depth studies of this trait.AbstractTo identify genomic regions that carry genetic factors controlling embryogenic potential of isolated microspores of rapeseed, marker segregations were analysed in a segregating population of haploid microspore-derived embryos and a BC1 population from a cross between ‘Express 617’ and ‘RS239’. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…It has actually been shown that homoeologous exchanges occur with higher frequency in resynthesized rapeseed genotypes or in crosses between such genotypes and natural rapeseed than in natural rapeseed itself Song et al 1995;Udall et al 2005;Szadkowski et al 2010;Chalhoub et al 2014). Furthermore Ecke et al (2015) found some evidence that such occurrences have happened during the development of the ISLs or already in the donor parent 'RS239'. About 40 % of the markers (186 out of 470 markers) on the diploid MDE map showed skewed segregations in the diploid MDE population.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has actually been shown that homoeologous exchanges occur with higher frequency in resynthesized rapeseed genotypes or in crosses between such genotypes and natural rapeseed than in natural rapeseed itself Song et al 1995;Udall et al 2005;Szadkowski et al 2010;Chalhoub et al 2014). Furthermore Ecke et al (2015) found some evidence that such occurrences have happened during the development of the ISLs or already in the donor parent 'RS239'. About 40 % of the markers (186 out of 470 markers) on the diploid MDE map showed skewed segregations in the diploid MDE population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a population of 323 doubled haploid ISLs, derived from microspores of BC 4 plants of the same cross with 'Express 617' as recurrent parent, was available to verify effects of specific genomic regions on the diploidization rate of microspores. The genetic characterization of the ISL population with 484 AFLP markers from a map constructed in a corresponding F 1 DH population (DH map) has been summarized in Ecke et al (2015); full details can be found in Nurhasanah (2010). Shortly, the ISLs carry an average of three donor segments, with a minimum of one and a maximum of nine.…”
Section: Plant Materials and Genetic Mapsmentioning
confidence: 99%
See 3 more Smart Citations